Geographies of development : an introduction to development studies - Potter, Robert B. (Routledge, 2018)
Now in its fourth edition, Geographies of Development: An Introduction to Development Studies remains a core, balanced and comprehensive introductory textbook for students of Development Studies, Development Geography and related fields. This clear and concise text encourages critical engagement by integrating theory alongside practice and related key topics throughout. It demonstrates informatively that ideas concerning development have been many and varied and highly contested - varying from time to time and from place to place.